KUPU-KUPU DI ATAS BUNGA – ANGIN MENARI MELALUI PADANG: MENYIMAK FILSAFAT SENI MARTIN HEIDEGGER - Yasintus T. Runesi (Program Studi Filsafat Agama Universitas Katolik Widya Mandira Kupang, 2019)
In his path of thinking, particularly from the 1930s onwards, Martin Heidegger firmly believed that Sein reveals itself, when human being, whom he termed as Dasein, awakened from his blindness of common sense and struggle for grasps his own authenticity. In this paper I examine Heidegger’s destruction of the work of art as a site of strife between art and politics in his text, Der Ursprung des Kunstwerkes. Heidegger’s position is complex: on the one hand, he acknowledges that Sein is a phenomenon beyond our horizon of understanding, Sein is all about not something particular; on the other hand, he insists that Sein’s presence through art inscribed in a certain particular identity, especially German volks. In response, I argue that the identification of Sein with a particular identity such as German volks, offers the truth that the politics itself is forged and instituted in and as work of art. Some conclusions will be drawn concerning the importance of the small dimension of Heidegger’s thought on art in contemporary politics.